Remarks from the 75th Anniversary Luncheon - Black, Barbara Aronstein (Columbia Journal of Gender and Law, 2003)
Laurie, thank you, as I’ve said to you on a number of occasions. Thank you: the words are totally inadequate, but they are the words I have, so again, thank you. Thank you for what you’ve done for the school, that David elucidated so very well, and thank you for what you’ve done for me, and for being my friend. I will try to make this reasonably brief, though not a s brief as a commencement address I was once asked to give. The invitation stated that I was to speak on any topic of my choice. Anything at all. For five minutes. Reporting this to one of my sons-I can’t remember which one-I said, “They say it has to be no longer than five minutes. What can I possibly say in five minutes that’s worth saying?” To which my son replied, “Did they say it has to be worth saying?”